The Influence of Transformational Leadership Style on Work Motivation and Its Implications for Teacher Performance in the Implementation of MTSS (Multi-Tier System of Support) at Lazuardi GCS School, Depok - Sari Kusuma Dewi; Muhammad Bukhori; Murtianingsih Murtianingsih (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
Teacher performance plays an important role in the success of inclusive education, especially in the implementation of the Multi-Tier System of Support (MTSS). MTSSis an approach that aims to provide academic, social-emotional, and behavioral support through tiered interventions. This study examines the effect of transformational leadership style on work motivation and its implications for teacher performance at Lazuardi Global Compassionate School (GCS) Depok. The research approach used is quantitative, with Smart Partial Least Square (SmartPLS) analysis. Data were collected from 35 teachers through a structured questionnaire. The results of the study indicate that: (1) transformational leadership style has a positive and significant effect on teacher work motivation, (2) transformational leadership style has a positive but insignificant effect on teacher performance, (3) work motivation has a positive and significant effect on teacher performance, and (4) transformational leadership style has a significant effect on teacher performance when mediated by work motivation. Considering that the direct effect of transformational leadership style on teacher performance is not significant, these results confirm the complete mediation of motivation on teacher performance. The results of this study recommend that school leaders provide professional development programs, as well as implement transparent performance evaluations to improve teacher effectiveness in inclusive education. Future research could explore additional variables, such as job satisfaction, school environment, and parental support, to gain a more comprehensive understanding of the factors that influence teacher performance in inclusive educational environments.